Complementary Therapies to Improve the Quality of Sleep in the Elderly: A Systematic Review - Ifansyah, M. Noor; Himmah, Elok Faiqotul; Pertiwi, Melinda Restu (D’Nursing and Health Journal (DNHJ), 2021)
Introduction: As humans get older, a degenerative aging process occurs which will have an impact on changes in humans. The changes that occur in the elderly can cause various kinds of disorders, one of which is sleep disturbance or insomnia. The aim of this systematic review is to gain a deeper understanding of complementary therapies to improve sleep quality in the elderly. Method: The design used by systematic review is that the reviewer looks for several articles through an electronic database, namely Scopus and ScienceDirect, the keywords used are "Therapy", "Sleep Quality" and "Elderly". Result: 16 selected articles, research conducted in Taiwan, Brazil, China, Singapore, Hong Kong, Korea, Japan and Iran found that the most widely used complementary therapy for improving the quality of sleep in the elderly is music therapy. Conclusion: The results of his study showed that the quality of sleep in the elderly improved with complementary therapy. For this reason, it is necessary to assess and provide complementary therapies such as music therapy regularly to improve sleep quality in the elderly.